COVID-19 CLUSTER IN PIKAT VILLAGE, KLUNGKUNG REGENCY, BALI, INDONESIA IN 2022 (Proceedings of the International Conference on Public Health, 2022)
Since October 2021, there have been no reports of additional COVID-19 cases inPikat Village. On January 21, 2022, a sick resident with symptoms of fever, headache, chestpain and shortness of breath was taken to Klungkung Hospital for treatment and PCR testresults confirmed COVID-19. This investigation aims to evaluate the existence of anoutbreak, describe the distribution and its risk factor. Descriptive design and case controlwere conducted immediately. Cases are residents with or without symptoms or closecontacts with positive PCR tests and controls are close contacts with negative PCR resultsData was collected using a questionnaire, and was analyzed univariate to multivariate. Theindex case is likely to be infected with COVID-19 while attending a massive traditionalceremony attended by many people from areas affected by COVID-19, 7 days beforesymptoms appeared. A total of 16 out of 17 (94.1%) close contacts of the index case wereconfirmed COVID-19. Tracing of 16 confirmed COVID-19 case showed that 5 out of 42(11.9%) close contacts also confirmed as COVID-19. The proportion of male and femalecases was balanced (54.5% vs. 45.5%), 50% were aged 20-60 years, and 68.2% lived in theindex case area. The common symptoms of cases were runny nose/stuffy nose (50%) andcough (50%), but 40.9% were asymptomatic. Multivariable analysis showed that notwearing a mask when outside the house (OR=4.425; 95% CI 1.206-16.233), not keeping adistance (OR=3.69; 95% CI 1.012-13.480), and poor hand hygiene practice (OR=5.99; 95%CI 1.521-23.613) is a risk factor for being infected with COVID-19. It was concluded thatthere had been a COVID-19 cluster in Pikat Village triggered by reduced compliance withhealth protocols because they thought that COVID-19 is no longer existed. Socialization ofhealth protocols is needed to prevent similar incidents.
Keywords: Keywords: Cluster, COVID-19, Village, Bali, Indonesia